2021
DOI: 10.2147/dmso.s313803
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Thyroid Hormone Levels and Macrovascular Complications in Euthyroid Type 2 Diabetic Patients

Abstract: Purpose The purpose of this study is to evaluate whether thyroid hormone in euthyroid patients with type 2 diabetes mellitus (T2DM) is associated with macrovascular complications. Patients and Methods The authors examined 311 patients enrolled from February 2019 to December 2019 in Tianjin Medical University Chu Hsien-I Memorial Hospital. A medical record review enabled the collection of demographic and anthropometric information. We classified the patients into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This discrepancy can be explained by the fact that the different definitions of macrovascular complications were used in above studies. That is, the macrovascular complications in the studies by Wang et al [ 38 ] and Hu et al [ 12 ] were defined as atherosclerosis from the aorta, coronary, basilar and carotid, while our current study mainly focused on carotid atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This discrepancy can be explained by the fact that the different definitions of macrovascular complications were used in above studies. That is, the macrovascular complications in the studies by Wang et al [ 38 ] and Hu et al [ 12 ] were defined as atherosclerosis from the aorta, coronary, basilar and carotid, while our current study mainly focused on carotid atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a study by Wang et al [ 38 ] displayed that diabetic patients with low-normal FT3 level were more likely to suffer from macrovascular complications than those with mid-and-high normal FT3 level. Hu et al [ 12 ] also revealed that there was a remarkable relation between diabetic macrovascular complications and normal FT3 (OR = 0.534, 95% CI 0.358–0.796). Partly consistent with the above studies, we found that patients in the lower FT3 quartiles were more prone to carotid atherosclerotic lesions than patients in the higher FT3 quartiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, current imaging has different deficiencies in the diagnosis of moderate stenosis (>50%) or severe stenosis (>70%) in asymptomatic CAS patients. For example, the preferred noninvasive diagnosis method of CAS in clinical practice is duplex ultrasound imaging, which is simple and safe, but it is easily affected by the level of operators, and it is expensive and not suitable for large-scale screening of the population [5][6][7] Therefore, the current priority is to identify and treat asymptomatic CAS patients as early as possible through noninvasive and low-cost methods to reduce the risk of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous study found that the low-normal FT3 and FT4 levels are associated with macrovascular complications in euthyroid type 2 diabetes mellitus patients. 17 However, the relationship between thyroid hormone and diabetic microvascular complications remains unclear. Therefore, to provide more comprehensive information for future research, we performed the present study to analyze the association of thyroid hormone with individual and any form of diabetic microvascular complications in euthyroid T2DM patients in the same population.…”
Section: Introductionmentioning
confidence: 99%